1997
DOI: 10.1180/minmag.1997.061.409.04
|View full text |Cite
|
Sign up to set email alerts
|

Composition of trioctahedral micas in the Karlovy Vary pluton, Czech Republic and a comparison with those in the Coruubian batholith, SW England

Abstract: Trioctahedral micas in the Karlovy Vary pluton range in composition from Fe-biotites in the granites of the Older Intrusive Complex (OIC) through siderophyllite and lithian siderophyllite to zinnwaldite in the granites of the Younger Intrusive Complex (YIC). Li + AlVI + Si would appear to substitute for Fe2+ + AlIV in biotite with a formula similar to that given in Henderson et al. (1989), but Li + Si appears to substitute for Fe2+ + AlIV in the Li-micas. In mica vs. host rock plots, Rb and F show positive lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The volatile constituents required can be generated from a subcrustal (mantle or crust/mantle interface) source above an active mantle. Stone et al (1997) suggested that one way of generating Li-mica granites would be by partial fusion of earlier granite residues, in which case the garnet-zinnwaldite phenocrysts association would be easily explicable. That is provided that there is sufficient heat in the granite-generating system to melt residues from an earlier formed granite (but see Creaser et aI., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The volatile constituents required can be generated from a subcrustal (mantle or crust/mantle interface) source above an active mantle. Stone et al (1997) suggested that one way of generating Li-mica granites would be by partial fusion of earlier granite residues, in which case the garnet-zinnwaldite phenocrysts association would be easily explicable. That is provided that there is sufficient heat in the granite-generating system to melt residues from an earlier formed granite (but see Creaser et aI., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors addressed this deficiency using additional methods. For example Stone et al (1988Stone et al ( , 1997, du Bray (1994), Ford et al (1995), Černý et al (1995), Breiter (2002) and Brigatti et al (2003) prepared monomineralic separates of mica via crushing, sieving, magnetic separation, separation in heavy liquids and handpicking. Separates with 95%-99% purity were analysed for Li using classical wet chemistry methods, e.g.…”
Section: Comparison Of Computed and Analysed LI Concentrations In Trimentioning
confidence: 99%
“…The concept of the essential replacement is linear. However, as emphasized by Stone et al (1997) and Tischendorf (1997), strictly speaking, the relations between cations in tetrahedral and octahedral sheets are not linear (e.g. Fig.…”
Section: The Concept Of Essential Replacement Is Suitable For Actual mentioning
confidence: 99%